Biometric Property Assessment of Bafra Sheep and Lambs - Sezen Ocak Yetişgin (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to compare the effects of biometric properties of Bafra sheep and lambs such as chest depth, chest width, chest circumference, rump height, height at withers, body length and body weight. Relationships were determined by Pearson correlation coefficient and Path analysis. As a result, it has been shown that biometric properties of Bafra sheep and lambs provide different results on live weight estimation. In addition, the relationships between biometric properties were not similar (r = -0.16).